2015
DOI: 10.4103/2229-3485.159938
|View full text |Cite
|
Sign up to set email alerts
|

A study of knowledge, attitudes, and practice of dental doctors about adverse drug reaction reporting in a teaching hospital in India

Abstract: Objective:The aim was to investigate the knowledge, attitudes, and practice of dental doctors about adverse drug reaction (ADR) reporting.Materials and Methods:In a cross-sectional study, questionnaire was administered to 95 dental doctors working in a teaching dental hospital attached to a medical college with an ADR monitoring center (AMC).Statistical Analysis Used:Descriptive statistics were used to analyze responses. The association of knowledge and attitude with respect to position of dentists was analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
31
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(46 citation statements)
references
References 22 publications
8
31
0
Order By: Relevance
“…This can be attributed to unfamiliarity of the study participants to the PvPI or lack in syllabus of the dental curriculum which covers this topic in detail. Similar results have been reported by Khan et al 15 and Palaian et al 16 among health-care professionals in Nepal and Rajesh et al 17 The low objective knowledge scores among dentists in this study were in agreement with the studies done by Khan et al 15 Contrasting results have been observed in a Graph 1: Term PV as understood by study participants study performed by dentists in the United Kingdom by Yip et al 18 Studies done among medical health professionals of developed countries like the United States and the United Kingdom have shown better knowledge scores. [19][20][21] In the United Kingdom and the United States, most of the medical and dental schools have introduced a yellow card ADR reporting system in the undergraduate syllabus and their skills are also assessed.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This can be attributed to unfamiliarity of the study participants to the PvPI or lack in syllabus of the dental curriculum which covers this topic in detail. Similar results have been reported by Khan et al 15 and Palaian et al 16 among health-care professionals in Nepal and Rajesh et al 17 The low objective knowledge scores among dentists in this study were in agreement with the studies done by Khan et al 15 Contrasting results have been observed in a Graph 1: Term PV as understood by study participants study performed by dentists in the United Kingdom by Yip et al 18 Studies done among medical health professionals of developed countries like the United States and the United Kingdom have shown better knowledge scores. [19][20][21] In the United Kingdom and the United States, most of the medical and dental schools have introduced a yellow card ADR reporting system in the undergraduate syllabus and their skills are also assessed.…”
Section: Discussionsupporting
confidence: 92%
“…Similar findings have been reported by Yip et al 18 Difficulty in deciding whether an ADR has occurred or not (52%) coupled with concerns that the report may be wrong (37%) is pinpointing toward the lack of knowledge and training of dentists in terms of identifying ADRs. Analogous findings of 65.5 and 27.5% were observed in studies done by Khan et al 15 and 80.9% and 81.8% among medical doctors by Gupta and Udupa 11 respectively.…”
Section: Discussionsupporting
confidence: 83%
“…However, there are limited data available, particularly among dental professionals in Turkey, and no studies conducted previously in our setting. Dental doctors are also involved in the prescription of many therapeutic interventions, including allopathic medicines such as local anesthetics, antibiotics, analgesics and antiinflammatory drugs (6,10). Antibiotics and analgesics are among the major causes of ADRs (6,11).…”
Section: Introductionmentioning
confidence: 99%
“…10 Another study done by Khan showed that deficiencies in knowledge and attitudes appear to be the underlying factor for under reporting by dental practitioners. 11 A study from Northern India reported that KAP regarding ADR monitoring was low and knowledge scores needed an improvement. 12 A study from Italy reported that doctors had little information concerning ADR and their reporting systems.…”
Section: Discussionmentioning
confidence: 99%